Interactive Effect of Meta-Cognitive Strategies-based Instruction in Mathematics and User experience on Student-Outcomes - Ingole, Meenakshi (Indian Journal of Educational Technology, 2020)
This paper attempts to ascertain the interactive effect of meta-cognitive strategies based instruction in mathematics and learner (user) experience design. This study focuses more on meta-cognitive experiences than meta-cognitive skills. For this purpose, an intervention programme based on meta-cognitive strategies of about 35 hours was developed for students of standard eighth spreading over eight weeks. The aim of the research was to ascertain whether meta-cognitive strategies-based instruction facilitates the academic achievement of students and user experience and interaction design decisions significantly affect how well on users (students) learn through meta-cognitive strategies. Structured tools were used in study. The participants of the study included 62 and 60 students in the experimental and control groups respectively. Students were found to be significantly influenced by the intervention programme as well as to help user interface in a way that supports and enhances the cognitive domain. The effect size of the intervention programme on academic achievement of students was found to be 1.30 and mathematics anxiety 1.084 was high in magnitude.